Physiology of innate immunity - Kelley, Keith W. (Henry Stewart Talks, 2012)
The varied roles innate immune cells play in the physiology of the entire body, The role of mononuclear myeloid cells in immunophysiology, Neuroendocrine stress responses, The gut-immune-brain axis, Update talk: Appetite, fever, sleep, cognition, anxiety, depression, etc. are all associated with the physiology and immunology fields, Update talk: Exercise, immunity, and mental health
Updated at 2022/01/30